Evaluación de la percepción de riesgo del consumo de psicofármacos durante el embarazo, en mujeres hospitalizadas en el Centro Hospitalario Pereira Rossell - Antonella Rossi; Gabriela Souto; Julietai Rijo; Mariana Odizzio; Mario Moraes; Gabriel González; Claudio Sosa (Anales de la Facultad de Medicina, 2015)
Most people and health professionals think that the use of psychotropic drugs should be avoided during pregnancy, specially during the first trimester. The choice of medications should be based on an individual analysis of risks and benefits of the given treatment. The principal aim of this study was to understand the perception of risk in the consumption of psychotropic drugs during pregnancy in post partum women hospitalized at the Centro Hospitalario Pereira Rossell (C.H.P.R). A descriptive observational study was conducted which consisted of a random sampling of a select population. 273 post partum women hospitalized in C.H.P.R. were surveyed in the period between July 11, 2014 and August 15, 2014. The mean age of the sample was 24 years. 90.5% of this sample considered that consuming these pharmaceuticals during pregnancy could lead to negative consequences on their child. Such consequence were quantified through a risk scale with values from 0 to 10 (considering 0 as the absence of the risk and 10 as the most harm possible) where 8,19 was the average obtained. With regard to prevalence, it was observed that only 7,7% had used psychotropic drugs during part of their life. 45.8% of the women stated that their doctors had not inquired them about consumption of these pharmaceuticals. As 90.5% of surveyed women stated that consuming psychotropic drugs during pregnancy could be a risk for their children, and given the average of 8.19 obtained through the risk scale, we concluded that the risk is overestimated. Pregnancy and post partum constitute risk factors that in vulnerable populations can produce depression and anxiety. Our results with overestimated risks of psychotropic drug use and lack of information from the doctors show the failure of the health system in this aspect. The metal health of this population must be priorized.